Planning agroecological transition for Food and Nutrition Security in the Muisca de Chía reservation. - Benavides Ocampo, Sergio Antony; Acevedo Osorio, Álvaro (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Society faces strong challenges to guarantee Food and Nutrition Security (FNS), especially in rural and indigenous communities. This study builds the bases for an agroecological transition process in order to contribute to the SAN´s guarantee in Muisca farming families in “Fonquetá y Cerca de Piedra” indigenous reservation in Chía-Cundinamarca (Colombia). The territorial context and the farming families limitations and potentialities, were analyzed to undertake a process towards the agroecological transition, which is conceived as a complex process of change from a conventional to an alternative form of sustainable agriculture based on agroecology way of producing food. A participatory methodology with a mixed approach was proposed, in order to identify categories of analysis based on an SAN analysis framework with an agroecological approach. The work was carried out with 13 families from the indigenous reservation dedicated to family farming with 45 people. 23% of family farms are planted with food crops, aromatic, medicinal and / or plants for ritual use and are generally located in the initial stages of the transition, although some have strengths in advanced stages. Despite negative situations such as the lack of economic support from the council or the municipality and the shortage of people to cultivate, there is a marked interest in producing food while preserving the environment and its culture, as well as a set of knowledge that should be promoted from the indigenous reservation to rebuild SAN in a collective way. The need to turn the institutional concept of FNS approached in this study towards the concept of Food Sovereignty is concluded, given its holistic, systemic, situated, inclusive and rights-based nature that promotes the agroecological transition.